ANALISIS AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA SMK MARITIM BATAM - ITA MUSTIKA; Andi Nadia Amaliah (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
ABSTRAK The purpose in this research is to know the procedures of Cash Receipt Accounting at Batam Maritime Vocational School, know the application of Cash Expenditure Accounting in Batam Maritime Vocational School and know the effectiveness of Cash Receipt and Expenditure Accounting in Batam Maritime Vocational School. The subject of the study is SMK Maritim Batam and the object of this research is Cash Receipt Accounting and Cash Expenditure Accounting. The data collection methods used are documentation methods and interview methods. The method used to describe problems related to the Cash Receipt Accounting procedure and the Cash Expenditure Accounting procedure is a descriptive analysis method. The results of this study show that: (1) The Application of Cash Receipt Accounting in Batam Maritime Vocational School has not been good enough. The functions related in the implementation of the Cash Receipt Accounting System are the cashier's part, the treasurer's part. The documents used are proof of cash acceptance, student payment notebooks. The accounting records used are general journals, cash books. (2) The application of Cash Expenditure Accounting in Batam Maritime Vocational School has not been good enough. The functions related in the implementation of Cash Expenditure Accounting are the cashier's part, the treasurer's part, the Principal. The documents used are proof of cash expenditure, financing approval letter, notes and invoices. The accounting records used are general journals, ledgers, cash books. (3) Accounting of Cash Receipts and Expenditures in Maritime SmK has not been effective enough.